(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Organic control of plant diseases, including the utilization of opposing microorganisms, offers a phenomenal contrasting option to synthetic control. An immense number of microorganisms exhibit in rhizosphere have been considered as critical in supportable farming on account of their biocontrol potential and capacity to advance plant growth. A diagram of the momentum status of research on the biocontrol of viral diseases by rhizobacteria is introduced in this. In this paper we discuss about the studies done in the field of Plant Growth Promoting Rhizobacteria.